Significance of destination fascination in destination marketing through movies - Tiwari, Veenus; Omar, Azizah; Mishra, Abhishek; Saad, Mazni (Cognizant Communication Corporation, 2025)
This study investigates how destination fascination influences behavioral intentions to visit film-featured destinations, with destination preference, attachment, and attitude serving as cognitive, affective, and conative mediators. Using attention restoration theory (ART) and the reasonable person model (RPM), a cross-sectional study involving 417 respondents was conducted to examine these relationships. The findings reveal that destination fascination positively impacts destination preference, deepens emotional attachment, and fosters favorable attitudes, significantly enhancing tourists’ intentions to visit. This research expands the understanding of films as powerful tools for destination marketing, particularly in domestic tourism, and highlights the importance of leveraging emotional and cognitive factors in promoting tourist destinations. The study contributes to tourism and environmental psychology by exploring destination fascination’s intrinsic and extrinsic outcomes, offering valuable insights for destination marketing strategies.